1996
DOI: 10.1002/ardp.19963290706
|View full text |Cite
|
Sign up to set email alerts
|

Sulfogriseofulvin Derivatives. Synthesis by [4+2]Cycloaddition, Structure, Properties, Crystal Structure Analysis, and Antifungal Activity of Spiro[1,3‐benzoxathiole‐2,1′‐cyclohex‐2′‐en]‐4′‐one 3,3‐Dioxides

Abstract: Syntheses of substituted, especially of fluoro substituted benzoxathiole 1,1-dioxides, are described. These derivatives were transformed via the Peterson olefination into substituted 2-alkylidene derivatives 27. Diels-Alder reactions of 27 with 1,1-dimethoxy- and 1-methoxy-3-trimethylsiloxy-1,3-butadiene (30, 32) gave sulfone analogues 31 of griseofulvin (named sulfogriseofulvins). From Z-27, a number of cis-isomers with the relative stereochemistry of griseofulvin (cis-31) was prepared, and from E-isomers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…All of these compounds, 2 intermediates, and the newly prepared 19 derivatives were confirmed by 1 H and 13 C NMR and MS as well as HRESIMS spectral data. Of the 22 analogues, 17 compounds (3b−3g, 5, 6a−6c, 6e−6k, and 7) are new based on searching in SciFinder web.…”
Section: ■ Results and Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…All of these compounds, 2 intermediates, and the newly prepared 19 derivatives were confirmed by 1 H and 13 C NMR and MS as well as HRESIMS spectral data. Of the 22 analogues, 17 compounds (3b−3g, 5, 6a−6c, 6e−6k, and 7) are new based on searching in SciFinder web.…”
Section: ■ Results and Discussionmentioning
confidence: 69%
“…Griseofulvin ( 1 ; Scheme ), a spirocyclic benzofuran-3-one natural antifungal product, was initially isolated from Penicillium griseofulvum in 1939 by Oxford et al It was the first oral antifungal drug in the treatment of dermatomycoses, such as tinea capitis (ringworm of the scalp) and tinea pedis (athlete’s foot), in animals and humans for decades. Griseofulvin has gained a lot of attention in research and academic circles; , more than 400 griseofulvin analogues have been synthesized and used for drug screening. In addition to the antifungal effect, griseofulvin exhibits various other biological activities, including anticancer and antiviral properties. Moreover, it is also useful against plant pathogenic fungi. Zhao et al reported that griseofulvin displayed clear inhibition of the growth of eight different plant pathogenic fungi. In our previously reported study, griseofulvin, as an isolated natural product, showed significant inhibitory activity against the pathogenic fungus Alternaria solani …”
Section: Introductionmentioning
confidence: 99%
“…They can be used as intermediates for pharmaceuticals and pesticides, and for the modification of polymers [17,18]. Certain sulfones are effective herbicides and others act as insecticides, and acaricides [19]; certain heterocyclic sulfones can be used as corrosion protection agents for metals [20].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclohex‐2‐enones are useful in the synthesis of organic compounds 1–5. Cyclohex‐2‐enone derivatives exhibit antifungal6 and anticancer7 activities. However, to our knowledge only two NMR spectral studies8, 9 have been reported on cyclohex‐2‐enones.…”
Section: Introductionmentioning
confidence: 99%